2015
DOI: 10.15713/ins.jcri.46
|View full text |Cite
|
Sign up to set email alerts
|

Determination of medical conditions afflicting patients visiting dental clinics: A population-based survey study

Abstract: Introduction:The evaluation of medical history questionnaire in dental clinics is essential to formulate a proper treatment plan in medically complex patients. Besides, it is also a source of information for future correspondence. The percentage of people suffering from chronic medical illness has been steadily increasing. Thus, it is imperative that the dentist will encounter patients with chronic illness in routine practice. Pre-administered questionnaires are the most commonly used and reliable method of ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 10 publications
4
5
0
Order By: Relevance
“…This study assessed the prevalence and various types of medical comorbidities amid patients in oral surgery clinics by examining the records of patients who were treated during a single academic period of 1 year at the College of Dentistry, Jazan University. The main findings of the study revealed that out of the total patients observed (n=640), the prevalence of patients with medical comorbidity was 27.5% (n=176), which is similar to that observed in recent studies by Lakhani et al (23.4%; n=1867) [ 41 ], Alonaizan et al (25.7%; n=1502) [ 42 ], Chandler et al (30.6%;n=716) [ 43 ], Shetty et al (33%; n=725) [ 38 ], Gaphor et al (35.24%; n=1200) [ 44 ], and Sanguansin et al (30.5%; n=712) [ 45 ]. Among these studies, however, the study by Lakhani et al was done in oral surgery patients for a similar time period (1 year), while the findings of Alonaizan et al [ 42 ] were observed in a Saudi academic dental hospital over a period of 6 years.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This study assessed the prevalence and various types of medical comorbidities amid patients in oral surgery clinics by examining the records of patients who were treated during a single academic period of 1 year at the College of Dentistry, Jazan University. The main findings of the study revealed that out of the total patients observed (n=640), the prevalence of patients with medical comorbidity was 27.5% (n=176), which is similar to that observed in recent studies by Lakhani et al (23.4%; n=1867) [ 41 ], Alonaizan et al (25.7%; n=1502) [ 42 ], Chandler et al (30.6%;n=716) [ 43 ], Shetty et al (33%; n=725) [ 38 ], Gaphor et al (35.24%; n=1200) [ 44 ], and Sanguansin et al (30.5%; n=712) [ 45 ]. Among these studies, however, the study by Lakhani et al was done in oral surgery patients for a similar time period (1 year), while the findings of Alonaizan et al [ 42 ] were observed in a Saudi academic dental hospital over a period of 6 years.…”
Section: Discussionsupporting
confidence: 84%
“…Studies across several nations have provided evidence of a low to high prevalence of health situations among dental outpatients, thereby stressing the need of considering regional population characteristics. A prevalence of low (11.7% in Nigeria [ 31 ], 12.2% in Thailand [ 32 ], 27.7% in Ireland) [ 33 ] to moderate (38% in India [ 34 ], 42% in West Indies) [ 35 ] to very high (73.7% in Iran [ 36 ], 86% in Australia [ 37 ]), across different time periods (1991 to 2020) substantiates not only the rising prevalence, but also supports the findings of the estimated proportion of non-communicable disease burden, with an expected increase to 57% by 2020 [ 38 ], and possibly sheds a new light on early age affliction of such diseases (below the age of 50 years). Two studies determining medical comorbidity prevalence in dentistry, in periodontal patients, from different provinces of Saudi Arabia also indicate a similar trend from low (10% [n=576] in year 2003) [ 39 ] to high (40.21% [n=455] in year 2017) [ 40 ] prevalence.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…45 Despite the oral cavity commonly serving as a mirroring indicator of underlying systemic disease, 46 prior studies documented low willingness of dental patients to disclose other stigmatized medical conditions, such as venereal diseases, tuberculosis, hepatitis, diabetes, and substance use. 29,[47][48][49][50][51] As such, frequent encounters in stigma-free dental settings and more direct exposure with the dentist may foster more trusting patient-dentist communication, as well as greater opportunities for patient education, that can alleviate patient concerns about medical disclosure. Alternatively, frequent dental care utilization may itself be a proxy for both access to dental care and trust and comfort in that dental practice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the direct clinical relationship between HIV infection and oral health problems is well established, and oral manifestations were identified as critical clinical markers in the early diagnosis and progression of HIV infection 45 . Despite the oral cavity commonly serving as a mirroring indicator of underlying systemic disease, 46 prior studies documented low willingness of dental patients to disclose other stigmatized medical conditions, such as venereal diseases, tuberculosis, hepatitis, diabetes, and substance use 29,47–51 . As such, frequent encounters in stigma‐free dental settings and more direct exposure with the dentist may foster more trusting patient–dentist communication, as well as greater opportunities for patient education, that can alleviate patient concerns about medical disclosure.…”
Section: Discussionmentioning
confidence: 99%